The placenta controls the physiology of pregnancy by increasing the half-life in blood and receptor activity of its secreted peptide hormones. (January 2018) - Lowry, Philip; Woods, Russell
Abstract : An efficient functioning placenta is essential for a healthy pregnancy and yet the way this is achieved has been the subject of much discussion and confusion, particularly with the occurrence of pathological conditions such as preeclampsia, morning sickness and hyperemesis/ptyalism gravidarum. We will attempt to explain the underlying physiology and the potential roles played by the placental tachykinins, neurokinin B and endokinin.